Unfinished business : screening the Italian Mafia in the new millennium - Renga, Dana, 1971- (University of Toronto Press, 2013)
"Unfinished Business is the first book to examine Italian mafia cinema of the past decade. It provides insightful analyses of popular films that sensationalize violence, scapegoat women, or repress the homosexuality of male protagonists. Dana Renga examines these works through the lens of gender and trauma theory to show how the films engage with the process of mourning and healing mafia-related trauma in Italy
Keywords: Gangster films -- Italy -- History and criticism.; Mafia in motion pictures.; Psychic trauma in motion pictures.; Motion pictures and women.; Gangster films -- Italy.; Films de gangsters -- Italie -- Histoire et critique.; Mafia au cinéma.; Traumatisme psychique au cinéma.; Cinéma et femmes.; Films de gangsters -- Italie.; PERFORMING ARTS -- Reference.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Gangster films; Mafia in motion pictures; Motion pictures and women; Psychic trauma in motion pictures; Italy; Mafia -- Motiv; Film; Italien; Criticism, interpretation, etc.